Public policy : politics, analysis, and alternatives - Kraft, Michael E.; Furlong, Scott R. (SAGE CQ Press, 2021)
"With the right information we can develop public policies that work better. All too often, public policy textbooks offer a basic grounding in the policy process without the benefit of integrating the use of policy analysis. Kraft and Furlong take a different tack. They want students to understand how and why policy analysis is used to assess policy alternatives-not only to question the assumptions of policy analysts, but to recognize how analysis is used in support of political arguments. To encourage critical and creative thinking on issues ranging from health care to climate change, the authors introduce and fully integrate an evaluative approach to policy. From a concise review of institutions, policy actors, and major theoretical models to discussion of the nature of policy analysis and its practice, the Kraft and Furlong show students how to employ evaluative criteria in six substantive policy areas. Students come away with the analytic tools they need to understand that the motivations of policy actors-both within and outside of government-influence a complex, yet comprehensible, policy agenda"--